2006
DOI: 10.3928/01484834-20060101-10
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating empowerment and stimulating scholarly dialogue using the World Café Model.

Abstract: <h4>Facilitating Empowerment and Stimulating Scholarly Dialogue Using the World Caf&eacute; Model</h4> <p>Student empowerment is the best vehicle for critical thinking and optimal learning, and enhances the development of nurses with the knowledge and skills required to navigate their way through the complex, shifting terrain of current nursing practice. Central to this process is scholarly dialogue, in which conversations are guided by an understanding of the state of the science in nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The idea of using a Café environment is to relax participants and explore topics of interest (Delaney, Daley and Lajoie, 2006) by encouraging a conversation which is meaningful and relevant (Pagliarini, 2006), sharing knowledge through experience, and sharing understanding (People and Participation, 2008). Through this, it is anticipated that participants will build a community (Schieffer et al , 2004b) and bring depth to the topic (The World Café, 2008), allowing for the production of rich data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea of using a Café environment is to relax participants and explore topics of interest (Delaney, Daley and Lajoie, 2006) by encouraging a conversation which is meaningful and relevant (Pagliarini, 2006), sharing knowledge through experience, and sharing understanding (People and Participation, 2008). Through this, it is anticipated that participants will build a community (Schieffer et al , 2004b) and bring depth to the topic (The World Café, 2008), allowing for the production of rich data.…”
Section: Resultsmentioning
confidence: 99%
“…. .’ (Delaney et al ., 2006, p. 46). It was argued that participants not only enjoyed the event, but also engaged in ‘lively conversations’ which enhanced the findings.…”
Section: The World Café Approachmentioning
confidence: 99%
“…Plenary sessions followed the World Café method, which facilitates conversations and cross-pollination of ideas in large groups (Delaney et al, 2006; Wiley et al, 2018). Specific questions designed to guide World Café conversations were based on works by Gunnlaugson et al (2013), Scharmer (2009), and Scharmer and Kaeufer (2010), and are explained below.…”
Section: Methodsmentioning
confidence: 99%
“…Delaney et al . (2006, p. 46) describe the World Café, a specialized form of the focus group approach to data collection, as enabling the exploration of current issues through ‘a living network of collaborative dialogue around questions that really matter’, and found that participants not only enjoyed the event, but also engaged in ‘lively conversations’, which enhanced the findings.…”
Section: World Cafémentioning
confidence: 99%